Analysis on digital forensics challenges and anti-forensics techniques in cloud computing - Vadlamudi, Divya; K. Thirupathi Rao, Dr; Vidyullatha, Pellakuri; ajasekharReddy, B (International Journal of Engineering and Technology, 2018)
In the modern life, there is a rapid increase in the usage of the technology. One reason of increasing the technology is usage of cloud. The mobile devices or any other technological devices mainly depend on cloud. The cloud can be accessible from anywhere. Cloud forensic process had introduced to help the investigators to find the evidence when the criminal attacks the cloud and to maintain the integrity and security for the data stored in the cloud. The increasing in the criminal attacks in cloud, made the investigators to find the latest methods for the forensic investigation process. Similarly in the same way the criminals also discover new ways to hide the source of evidences. This causes damage to the investigation process and is called anti-forensics. To hide the sources anti-forensic techniques are used and research must be done against the anti-forensics techniques in cloud environment. In this paper we focused mainly on detailed study on various challenges in cloud forensic and anti-forensic techniques.Â